Correction: Enabling methanol oxidation by an interacting hybrid nanosystem of spinel Co3O4 nanoparticle decorated MXenes. Issue 15 (1st April 2022) - Baruah, Kashmiri; Deb, Pritam
Abstract : Correction for 'Enabling methanol oxidation by an interacting hybrid nanosystem of spinel Co3 O4 nanoparticle decorated MXenes' by Kashmiri Baruah et al., Dalton Trans., 2022, 51, 4324–4337, DOI: ; 10.1039/D1DT03671H .